Odpowiedzi

2009-12-14T21:22:36+01:00
A) 8(a - 0,5) - a(a + 2,5) = dla a = 3,5

8(3,5 - 0,5) - 3,5(3,5 + 2,5) = 28 - 4 - 12,25 - 8,75 = 3

b) a - b (a + b) (2a - b) = dla a = 1,5 i b = 0,5

1,5 - 0,5(1,5 + 0,5)*(3 - 0,5) = 1,5 - (0,75 + 0,25)*(2,5) = 1,5 - (1*2,5) = 1,5 - 2,5 = -1

c) 3a(do kwadratu) - 6a + 4 : a(do kwadratu) - 9a + 6 = dla a = 2/3 (w ułamku)

3a² - 6a + 4:a² - 9a + 6 = 3*(2/3)² - 6*2/3 + 4:(2/3)² - 9*2/3 + 6 = 12/9 - 12/3 + 4*9/4 - 18/3 + 6 = 12/9 - 36/9 + 36/4 - 18/3 + 6 = -24/9 + 9 - 6 + 6 = -24/9 +9 = -24/9 + 81/9 = 57/9 = 6 3/9 = 6 1/3
Najlepsza Odpowiedź!
2009-12-14T21:24:45+01:00
A) 8(3,5 - 0,5) - 3,5(3,5+2,5) = 8*3 - 3,5*6 = 24 - 21 = 3

b) 1,5 - 0,5(1,5 + 0,5)(2*1,5 - 0,5) = 1,5 - 0,5 * 2 * 2,5 = 1,5 - 2,5 = -1

c) 3*(²/₃)² - 6* ²/₃ + 4: (²/₃)² - 9*²/₃ + 6 = 3* ⁴/₉ - 4 + 4:⁴/₉ - 6 +6 =
⁴/₃ - 4 + 9= 1¹/₃ + 5 = 6¹/₃
1 5 1